Degradable material, three-dimensional article and preparation method thereof

CN122958833APending Publication Date: 2026-10-23SUZHOU CHANGKAI PLASTIC MOLDING PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611047422.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,现有技术仍存在以下不足:(1)制品形态限制:多数研究集中于薄膜类产品,对于立体制品的阻隔改性研究少,而二者由于形态差异,导致成型工艺将会有较大挑战;(2)工艺复杂:多层共挤等工艺设备投资大,且难以实现GO在特定层位的精确定位

Benefits of technology

第一,本申请提供的可降解材料,通过将PBAT、GO、PLA、三层依次复合,形成产品阻隔性能更好,且层间不易脱落,具有良好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of degradable material preparation, in particular to a degradable material, a three-dimensional product and a preparation method thereof. Specifically, the degradable material comprises a base part and a structure part; the base part comprises a PBAT layer and an oxidized graphene layer located on a first surface of the PBAT layer; the structure part comprises a PLA layer; the PLA layer is combined with the PBAT layer through the oxidized graphene layer. The material is prepared through steps of preparing an oxidized graphene dispersion solution, coating the oxidized graphene, preforming and fusing the PLA. In the application, the PBAT, GO, PLA and three layers are sequentially compounded to form a product which has better barrier performance and is not easy to fall off between layers, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of biodegradable material preparation technology, specifically to a biodegradable material, a three-dimensional article, and a method for preparing the same. Background Technology

[0002] With the growing severity of global plastic pollution, the research and application of biodegradable materials have received widespread attention. Polylactic acid (PLA) and polybutylene adipate-co-terephthalate (PBAT) are two important biodegradable polymers.

[0003] PLA has high strength and modulus, but its inherent gas barrier properties are poor, making it difficult to meet the requirements of high-performance packaging; while PBAT has good flexibility and processing properties, but its barrier properties against oxygen and water vapor are also poor, showing a significant gap compared with traditional petroleum-based films (such as polyethylene and polypropylene).

[0004] In the existing technology, researchers have explored a variety of modification strategies to improve the barrier properties of biodegradable materials. For example, blending PLA with PBAT, adding nanofillers such as montmorillonite or graphene oxide (GO), and multilayer co-extrusion. However, the existing technology still has the following shortcomings: (1) Product shape limitation: Most studies focus on thin film products, and there is little research on barrier modification of three-dimensional products. Due to the difference in shape, the molding process will be more challenging; (2) Complex process: Multilayer co-extrusion and other processes require large investment in equipment and it is difficult to achieve precise positioning of GO in specific layers.

[0005] In view of the above, this application is hereby submitted. Summary of the Invention

[0006] The purpose of this application is to provide a biodegradable material, a three-dimensional article, and a method for preparing the same, in order to solve at least one of the technical problems mentioned in the background art.

[0007] Specifically, in a first aspect, this application provides a biodegradable material comprising: The base includes a PBAT layer and a graphene oxide layer located on the first surface of the PBAT layer; Structural components, including the PLA layer; The PLA layer and the PBAT layer are bonded together by a graphene oxide layer.

[0008] Preferably, in the biodegradable material, the PBAT layer comprises 30-70 parts by mass and the graphene oxide layer comprises 0.1-1 parts by mass. More preferably, the PBAT layer comprises 55-60 parts and the graphene oxide layer comprises 0.4-0.6 parts by mass.

[0009] Preferably, the thickness of the PBAT layer is 10-100 μm, more preferably 30-50 μm.

[0010] Preferably, the thickness of the PLA layer is 10-100 μm, more preferably 20-50 μm.

[0011] Preferably, the thickness of the graphene oxide barrier layer is 50-200 nm, more preferably 91-185 nm.

[0012] Understandably, the thickness of the PLA layer in the biodegradable material provided in the first aspect of this application can be adjusted according to actual needs. Optionally, the mass fraction of the PLA layer is not less than 30 parts, but is 30-70 parts, 100-200 parts, or 300-500 parts, etc.; correspondingly, the thickness of the PLA layer is 20-50 μm, or 60-150 μm, or 150-400 μm, etc.

[0013] A second aspect of this application provides a method for preparing a biodegradable material as described in the first aspect, comprising the steps of: To prepare a graphene oxide dispersion, graphene oxide powder was dispersed in a solvent and ultrasonically treated to obtain a uniform graphene oxide dispersion with a concentration of 1-1.8 mg / mL. Graphene oxide coating: The graphene oxide dispersion is applied at a concentration of 5-10 g / m³. 2 The PBAT substrate film is uniformly coated on the surface of the PBAT film, and the solvent is removed by drying. A graphene oxide barrier layer is formed on the surface of the PBAT film to obtain a PBAT / GO composite film, or substrate. Pre-forming involves placing the PBAT / GO composite film inside the cavity of an injection mold, ensuring the composite film adheres tightly to the inner wall of the mold to form a pre-formed body that matches the shape of the mold; the graphene oxide barrier layer of the composite film faces the inner side of the mold cavity. PLA is fused together by injecting PLA melt into a mold with PBAT / GO composite film bonded together, so that PLA melt comes into contact with the surface of the graphene oxide barrier layer of the preform. Under the action of injection pressure and temperature, PLA melt and PBAT / GO composite film are tightly bonded together. After cooling, the mold is removed to obtain a laminated three-dimensional product including a base and structural parts.

[0014] Preferably, in the step of preparing graphene oxide dispersion, the ultrasonic frequency is 68-120 kHz and the ultrasonic time is 1-3 h.

[0015] Preferably, in the step of preparing the graphene oxide dispersion, the solvent is selected from water, ethanol, or a combination of both.

[0016] Preferably, in the step of preparing the graphene oxide dispersion, after uniformly dispersing the graphene oxide powder in deionized water, 0.5-0.8 wt% of the silane coupling agent KH550 (γ-aminopropyltriethoxysilane) and 0.1-0.2 wt% of polyvinyl alcohol are added, and the mixture is ultrasonicated at a frequency of 68-120 kHz for 1-3 hours. Preferably, the PBAT substrate film is prepared by blow molding or casting and has a thickness of 30-50 μm.

[0017] Preferably, in the graphene oxide coating step, the thickness of the graphene oxide barrier layer formed on the surface of the PBAT film is 50-200 nm.

[0018] Preferably, after the graphene oxide coating step, the obtained PBAT / GO composite film is subjected to unidirectional or bidirectional stretching treatment at 60-90°C, with a stretching rate of 1.5-2 times, so that the graphene oxide sheets are oriented and aligned in the film plane.

[0019] Preferably, in the preforming step, vacuum forming is used to tightly adhere the composite film to the inner wall of the mold, with a vacuum degree of -0.05 to -0.1 MPa and a heating temperature of 60-100°C, so that the PBAT film softens but does not melt.

[0020] Preferably, in the PLA fusion step, the PLA injection temperature is 190-210℃, the injection pressure is 80-120MPa, the injection speed is 40-80mm / s, and the holding time is 10-30s.

[0021] Preferably, in the PLA fusion step, the heat of the PLA melt causes the graphene oxide layer on the surface of the PBAT / GO composite film to form an interfacial bond with the PLA, while the side of the PBAT film in contact with the mold retains its original shape.

[0022] Preferably, the PLA fusion step includes, In the first stage of injection molding, with the mold closed and under vacuum, 5-8 parts of PLA melt are injected into the mold cavity at a uniform speed through the injection molding machine. First, control the first barrel to control the PLA injection temperature at 170-175℃, the injection pressure at 100-110MPa, and the injection speed at 10-20 mm / s. Two-stage injection molding, without the need for holding pressure and cooling, immediately switches the barrel to control the PLA injection temperature at 190-210℃, the injection pressure at 80-120MPa, and the injection speed at 40-80 mm / s. The remaining injected PLA melt makes full contact with the surface of the graphene oxide layer of the preform. Under the synergistic effect of high temperature and high pressure, a strong interfacial bond is formed between the PLA and the graphene oxide layer. After the PLA melt injection is completed, the pressure is held for 10-30 seconds. Then, cooling treatment is performed, and after cooling to room temperature, the mold is opened and the product is removed.

[0023] A third aspect of this application provides a three-dimensional article prepared from the biodegradable material of the first aspect of this application.

[0024] Preferably, the three-dimensional article is a lunch box, tray, cup, bowl, or any plastic container with a three-dimensional shape.

[0025] A fourth aspect of this application provides a three-dimensional article obtained by the preparation method described in the second aspect of this application.

[0026] Preferably, the three-dimensional article is a lunch box, tray, cup, bowl, or any plastic container with a three-dimensional shape.

[0027] In summary, this application has the following beneficial effects: First, the biodegradable material provided in this application, by sequentially compounding PBAT, GO, and PLA into three layers, forms a product with better barrier properties and is less prone to detachment between layers, thus showing good application prospects.

[0028] Secondly, the biodegradable material preparation method provided in this application optimizes the arrangement and orientation of the GO layer by coating GO onto the surface of PBAT. Compared with direct melt blending, it has a better barrier effect and the process is simple and conducive to promotion.

[0029] Third, the biodegradable material preparation method provided in this application can further improve the stability of the GO layer by performing stepwise injection molding of PLA, which is beneficial to improving the barrier performance of the finished product. Detailed Implementation

[0030] The terminology used in this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The singular forms “a,” “the,” and “the” used in this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any or all possible combinations of one or more of the associated listed items.

[0031] The present application will be described in detail below through examples.

[0032] In existing technologies, blends of PLA and PBAT suffer from limitations in product morphology, complex processes, and the tendency for GO to agglomerate. Therefore, to address at least one of these technical problems, this invention provides a biodegradable material comprising: a base layer including a PBAT layer and a graphene oxide layer on the first surface of the PBAT layer; and a structural portion including a PLA layer; wherein the PLA layer and the PBAT layer are bonded together by the graphene oxide layer. According to this invention, by sequentially compounding PBAT, GO, and PLA layers, the resulting product exhibits better barrier properties and is less prone to interlayer detachment, demonstrating promising application prospects.

[0033] To better understand the above technical solutions, the following detailed descriptions will be provided in conjunction with specific implementation methods. Those skilled in the art should also understand that the reaction times and drug dosages involved in this application cannot be absolutely precise in actual production, but are all within the allowable error range. For example, if the desired sample heating time is 30 minutes, the actual operation may be 30 minutes plus or minus 1 second; if the desired sample weight is 30g, the actual weight may be 30.001g or 29.998g.

[0034] In this application, the thickness of the graphene oxide layer formed on the surface of the PBAT film is detected using existing techniques, such as FE-SEM fracture surface observation: The PBAT / GO composite films prepared in the examples or comparative examples were subjected to cold brittle fracture in liquid nitrogen, maintaining a clean fracture surface. The cross-section was then observed using a high-resolution field emission scanning electron microscope at an accelerating voltage of 10 kV. The thickness of the GO interlayer at five different locations was read and statistically analyzed using the image scale at high magnification, and the average value was taken.

[0035] Example 1 Preparation of graphene oxide dispersion: 0.4 parts of graphene oxide powder were uniformly dispersed in deionized water and ultrasonically treated at a frequency of 120 kHz for 1 h to prepare a graphene oxide dispersion with a concentration of 1.0 mg / mL for later use.

[0036] Graphene oxide coating: 55 parts by weight of commercially available PBAT film with a thickness of 30 μm, prepared by blow molding, were selected. Before use, the film underwent corona treatment to ensure a surface tension of at least 42 dyn / cm. The prepared graphene oxide dispersion was coated using a wire rod coating method at a concentration of 5 g / m³. 2 The coating amount was uniformly applied to the corona-treated PBAT film surface. After coating, the film was dried in a 60°C hot air drying oven for 5 minutes. The thickness of the graphene oxide layer formed on the PBAT film surface was measured to be 91 nm. The coating amount refers to the area of ​​the dried GO solids.

[0037] Stretching treatment: The PBAT film coated with graphene oxide layer is subjected to uniaxial stretching treatment at 60 ℃, and the stretching ratio is controlled at 1.5 times to achieve orientation alignment of the graphene oxide sheets, thus obtaining a PBAT / GO composite film for later use.

[0038] Pre-forming: The PBAT / GO composite film prepared above is cut to a size that matches the injection mold and placed into the mold cavity, ensuring that the graphene oxide layer of the PBAT / GO composite film faces the inside of the mold cavity (i.e., towards the direction of the PLA melt to be injected later); the vacuum system is activated, and the vacuum degree inside the mold is adjusted to -0.05 MPa, while the injection mold is heated and the mold temperature is controlled at 60°C, so that the PBAT film softens but does not melt; under the action of vacuum suction, the softened PBAT / GO composite film adheres tightly to the inner wall of the mold, forming a pre-formed body consistent with the shape of the mold, while maintaining the vacuum state of the mold.

[0039] PLA fusion: Maintaining the mold closed and under vacuum, 40 parts of molten PLA are injected uniformly into the mold cavity using an injection molding machine. The PLA injection temperature is controlled at 190℃, the injection pressure at 120MPa, and the injection speed at 40 mm / s. The injected molten PLA makes full contact with the surface of the graphene oxide layer of the preform. Under the synergistic effect of high temperature and high pressure, a strong interfacial bond forms between the PLA and the graphene oxide layer. After the PLA melt injection is complete, the pressure is held for 10 seconds. Cooling is then performed, and after cooling to room temperature, the mold is opened, and the product is removed.

[0040] Example 2 Preparation of graphene oxide dispersion: 0.5 parts of graphene oxide powder were uniformly dispersed in deionized water and ultrasonically treated at a frequency of 100 kHz for 2 h to obtain a graphene oxide dispersion with a concentration of 1.5 mg / mL for later use.

[0041] Graphene oxide coating: A commercially available PBAT film with a thickness of 40 μm, prepared by blow molding, was selected in 55 parts by weight. Before use, it underwent corona treatment to ensure that the surface tension of the film reached above 42 dyn / cm. The prepared graphene oxide dispersion was coated using a wire rod coating method at a rate of 8 g / m². 2 The coating amount was uniformly applied to the corona-treated PBAT film surface. After coating, the film was dried in a 70°C hot air drying oven for 4 minutes. The thickness of the graphene oxide layer formed on the PBAT film surface was measured to be 152 nm. The coating amount refers to the area of ​​the dried GO solids.

[0042] Stretching treatment: The PBAT film coated with graphene oxide layer is subjected to uniaxial stretching treatment at 80 ℃, and the stretching ratio is controlled at 1.8 times to achieve orientation alignment of the graphene oxide sheets, thus obtaining a PBAT / GO composite film for later use.

[0043] Pre-forming: The PBAT / GO composite film prepared above is cut to a size that matches the injection mold and placed into the mold cavity, ensuring that the graphene oxide layer of the PBAT / GO composite film faces the inside of the mold cavity (i.e., towards the direction of the PLA melt to be injected later); the vacuum system is activated to adjust the vacuum degree inside the mold to -0.08MPa, while the injection mold is heated and the mold temperature is controlled at 80℃, so that the PBAT film softens but does not melt; under the action of vacuum suction, the softened PBAT / GO composite film adheres tightly to the inner wall of the mold, forming a pre-formed body consistent with the shape of the mold, while maintaining the vacuum state of the mold.

[0044] PLA fusion: Maintaining the mold closed and under vacuum, 45 parts of molten PLA are injected uniformly into the mold cavity using an injection molding machine. The PLA injection temperature is controlled at 200℃, the injection pressure at 100MPa, and the injection speed at 60 mm / s. The injected molten PLA makes full contact with the surface of the graphene oxide layer of the preform. Under the synergistic effect of high temperature and high pressure, a strong interfacial bond forms between the PLA and the graphene oxide layer. After the PLA melt injection is completed, the pressure is held for 15 seconds. Cooling is then performed, and after cooling to room temperature, the mold is opened, and the product is removed.

[0045] Example 3 Preparation of graphene oxide dispersion: 0.6 parts of graphene oxide powder were uniformly dispersed in deionized water and ultrasonically treated at a frequency of 68 kHz for 3 hours to obtain a graphene oxide dispersion with a concentration of 1.8 mg / mL for later use.

[0046] Graphene oxide coating: A commercially available PBAT film with a thickness of 50 μm, prepared by blow molding, was used in a quantity of 60 parts by weight. Before use, it underwent corona treatment to ensure that the surface tension of the film reached at least 42 dyn / cm. The prepared graphene oxide dispersion was coated using a wire rod coating method at a rate of 10 g / m². 2 The coating amount was uniformly applied to the corona-treated PBAT film surface. After coating, it was placed in an 80℃ hot air drying machine for 5 minutes. The thickness of the graphene oxide layer formed on the PBAT film surface was measured to be 185 nm. The coating amount refers to the mass area of ​​the dried GO solids.

[0047] Stretching treatment: The PBAT film coated with graphene oxide layer is subjected to uniaxial stretching treatment at 90°C, and the stretching ratio is controlled to 2 times to achieve orientation alignment of the graphene oxide sheets, thus obtaining a PBAT / GO composite film for later use.

[0048] Pre-forming: The PBAT / GO composite film prepared above is cut to a size that matches the injection mold and placed into the mold cavity, ensuring that the graphene oxide layer of the PBAT / GO composite film faces the inside of the mold cavity (i.e., towards the direction of the PLA melt to be injected later); the vacuum system is activated, and the vacuum degree inside the mold is adjusted to -0.1MPa. At the same time, the injection mold is heated and the mold temperature is controlled at 100℃, so that the PBAT film softens but does not melt; under the action of vacuum suction, the softened PBAT / GO composite film adheres tightly to the inner wall of the mold, forming a pre-formed body consistent with the shape of the mold, while maintaining the vacuum state of the mold.

[0049] PLA fusion: Maintaining the mold closed and under vacuum, 45 parts of molten PLA are injected uniformly into the mold cavity using an injection molding machine. The PLA injection temperature is controlled at 210℃, the injection pressure at 80MPa, and the injection speed at 80 mm / s. The injected molten PLA makes full contact with the surface of the graphene oxide layer of the preform. Under the synergistic effect of high temperature and high pressure, a strong interfacial bond forms between the PLA and the graphene oxide layer. After the PLA melt injection is completed, the pressure is held for 30 seconds. Cooling is then performed, and after cooling to room temperature, the mold is opened, and the product is removed.

[0050] Example 4 The preparation process in this embodiment is basically the same as that in Example 2, the only difference being: In the process of preparing graphene oxide dispersion, 0.5 wt% of silane coupling agent KH550 was added to the prepared graphene oxide dispersion, and ultrasonic treatment was performed at a frequency of 100 kHz for 2 h.

[0051] Example 5 The preparation process in this embodiment is basically the same as that in Example 2, the only difference being: In the process of preparing graphene oxide dispersion, 0.5 wt% of silane coupling agent KH550 and 0.1 wt% of polyvinyl alcohol were added to the prepared graphene oxide dispersion, and ultrasonic treatment was performed at a frequency of 100 kHz for 2 hours.

[0052] Example 6 The preparation process of this embodiment is basically the same as that of Example 1, the only difference being: In the PLA fusion step, while the mold is closed and under vacuum, 5 parts of PLA melt are injected into the mold cavity at a uniform speed through the injection molding machine. First, the first barrel is controlled to set the PLA injection temperature to 170℃, the injection pressure to 100MPa, and the injection speed to 10mm / s to form a thin film. Without the need for pressure holding and cooling, the barrel is immediately switched to control the PLA injection temperature at 190℃, the injection pressure at 120MPa, and the injection speed at 40 mm / s. The injected 35 parts of PLA melt make full contact with the surface of the graphene oxide layer of the preform. Under the synergistic effect of high temperature and high pressure, a strong interfacial bond is formed between the PLA and the graphene oxide layer. After the PLA melt injection is completed, the pressure is held for 10 seconds. Then, cooling treatment is performed, and after cooling to room temperature, the mold is opened and the product is removed.

[0053] Example 7 The preparation process in this embodiment is basically the same as that in Example 2, the only difference being: In the PLA fusion step, while the mold is closed and under vacuum, 6 parts of PLA melt are injected into the mold cavity at a uniform speed through the injection molding machine. First, the first barrel is controlled to set the PLA injection temperature to 175℃, the injection pressure to 110MPa, and the injection speed to 20mm / s, forming a thin film. Without the need for pressure holding and cooling, the barrel is immediately switched to control the PLA injection temperature at 200℃, the injection pressure at 100MPa, and the injection speed at 60 mm / s. The injected 39 parts of PLA melt make full contact with the surface of the graphene oxide layer of the preform. Under the synergistic effect of high temperature and high pressure, a strong interfacial bond is formed between the PLA and the graphene oxide layer. After the PLA melt injection is completed, the pressure is held for 15 seconds. Then, cooling treatment is performed, and after cooling to room temperature, the mold is opened and the product is removed.

[0054] Example 8 The preparation process in this embodiment is basically the same as that in Example 3, except that: In the PLA fusion step, while the mold is closed and under vacuum, 8 parts of PLA melt are injected into the mold cavity at a uniform speed through the injection molding machine. First, the first barrel is controlled to set the PLA injection temperature to 170℃, the injection pressure to 100MPa, and the injection speed to 20mm / s, forming a thin film. Without the need for pressure holding and cooling, the barrel is immediately switched to control the PLA injection temperature at 210℃, the injection pressure at 80MPa, and the injection speed at 80 mm / s. The injected 37 parts of PLA melt make full contact with the surface of the graphene oxide layer of the preform. Under the synergistic effect of high temperature and high pressure, a strong interfacial bond is formed between the PLA and the graphene oxide layer. After the PLA melt injection is completed, the pressure is held for 30 seconds. Then, cooling treatment is performed, and after cooling to room temperature, the mold is opened and the product is removed.

[0055] Example 9 The preparation process in this embodiment is basically the same as that in Example 7, except that: In the process of preparing graphene oxide dispersion, 0.5 wt% of silane coupling agent KH550 was added to the prepared graphene oxide dispersion, and ultrasonic treatment was performed at a frequency of 100 kHz for 2 h.

[0056] Example 10 The preparation process in this embodiment is basically the same as that in Example 7, except that: In the process of preparing graphene oxide dispersion, 0.5 wt% of silane coupling agent KH550 and 0.1 wt% of polyvinyl alcohol were added to the prepared graphene oxide dispersion, and ultrasonic treatment was performed at a frequency of 100 kHz for 2 hours.

[0057] Example 11 The preparation process in this embodiment is basically the same as that in Example 7, except that: In the process of preparing graphene oxide dispersion, 0.8 wt% of silane coupling agent KH550 and 0.2 wt% of polyvinyl alcohol were added to the prepared graphene oxide dispersion, and ultrasonic treatment was performed at a frequency of 100 kHz for 2 hours.

[0058] Example 12 The preparation process of this embodiment is basically the same as that of Example 10, the only difference being: In the process of preparing graphene oxide dispersion, 0.5 wt% of silane coupling agent KH550 and 0.1 wt% of sodium carboxymethyl cellulose were added to the prepared graphene oxide dispersion, and the dispersion was ultrasonically treated at a frequency of 100 kHz for 2 h.

[0059] Example 13 The preparation process of this embodiment is basically the same as that of Example 10, the only difference being: In the process of preparing graphene oxide dispersion, 0.8 wt% of silane coupling agent KH550 and 0.2 wt% of sodium carboxymethyl cellulose were added to the prepared graphene oxide dispersion, and the dispersion was ultrasonically treated at a frequency of 100 kHz for 2 h.

[0060] Comparative Example 1: Pure PLA Injection Molded Products Pure PLA granules were used to prepare injection molded products of the same size, using the same injection molding process as in Example 2.

[0061] Comparative Example 2: PBAT Vacuum Forming Products Vacuum-formed products of the same size were prepared by vacuum forming using pure PBAT film with a thickness of 40μm, without PLA injection molding layer or GO coating.

[0062] Comparative Example 3: PLA / PBAT Direct Composite The preparation process of this comparative example is basically the same as that of Example 2, except that: Instead of coating the PBAT film with a graphene oxide layer, the PBAT film is directly vacuum-formed and then injection-molded with PLA.

[0063] Comparative Example 4: GO-modified PLA injection molded products The preparation process of this comparative example is basically the same as that of Example 2, except that: Graphene oxide and PLA were melt-blended to prepare PLA / GO composite granules with a graphene oxide content of 0.5 wt%. Then, products of the same size without PBAT layer were prepared by injection molding.

[0064] Comparative Example 5: PLA / GO and PBAT Composite The preparation process of this comparative example is basically the same as that of Example 2, except that: PLA / GO composite granules with a graphene oxide content of 0.5 wt% were prepared by melt blending graphene oxide and PLA. The PBAT film was then vacuum-formed, followed by injection molding of the PLA / GO composite.

[0065] Comparative Example 6 The preparation process of this comparative example is basically the same as that of Example 7, except that: In the PLA fusion step, while the mold is closed and under vacuum, the PLA melt is injected into the mold cavity at a uniform speed through the injection molding machine. First, the first barrel is controlled to control the PLA injection temperature at 190℃, the injection pressure at 110MPa, and the injection speed at 20 mm / s to form a thin film. No pressure holding and cooling are required. The barrel is immediately switched to control the PLA injection temperature at 190℃, the injection pressure at 100MPa, and the injection speed at 60 mm / s. The injected PLA melt makes full contact with the surface of the graphene oxide layer of the preform. Under the synergistic effect of high temperature and high pressure, a strong interfacial bond is formed between the PLA and the graphene oxide layer. After the PLA melt injection is completed, the pressure is held for 15 seconds. Then, cooling treatment is performed. After cooling to room temperature, the mold is opened and the product is removed.

[0066] Example 14 Performance Testing The water vapor transmission rate, oxygen transmission rate, interlayer bonding force, and biodegradability of the products obtained in Examples 1-13 and Comparative Examples 1-5 were determined according to the following methods.

[0067] Water vapor transmission rate: According to GB / T 1037-2021 standard, samples were cut from the wall of the product for testing under the conditions of 38℃ and 90%RH.

[0068] Oxygen permeability: According to GB / T 1038.1-2022 standard, samples were cut from the wall of the product for testing under the conditions of 23℃ and 50%RH.

[0069] Interlayer bonding strength: The T-type peel strength between the PBAT layer and the PLA layer was tested in accordance with GB / T 2791-1995 standard.

[0070] Biodegradability: In accordance with GB / T 19277.1-2011 standard, the biodegradability of the product was tested under controlled composting conditions for 28 days.

[0071] The results of the above performance tests are shown in Table 1.

[0072] Table 1 Performance test results of Examples 1-13 and Comparative Examples 1-6

[0073] Based on the test results in Table 1, those skilled in the art should understand that: First, the product composed of PBAT / GO / PLA prepared in this application has better barrier properties compared with the prior art. Comparing Examples 1-3 with Comparative Examples 1-3, the water vapor transmission rate, oxygen transmission rate, or interlayer bonding strength of the PLA products, PBAT products, or products composed of both in the prior art are all weaker than those obtained in the examples of this application, indicating that the composite product prepared by the scheme of this application can better isolate water vapor and gas, and has better application prospects.

[0074] Second, the PBAT / GO / PLA product obtained by the preparation method proposed in this application is of superior quality compared to products obtained by existing preparation methods. Comparing Examples 1-3 and Comparative Examples 4-5, the barrier effects of PLA / GO or PBAT / GO / PLA prepared by direct melt blending are inferior to those of the products prepared by the method of this application. This indicates that in the preparation method proposed in this application, the graphene oxide coating process enables better orientation and alignment, forming a more complex labyrinth structure.

[0075] Third, the addition of silane coupling agent KH550 and polyvinyl alcohol to the graphene oxide dispersion is beneficial to its dispersion stability. Comparing Example 5 with Example 2, or Example 10-11 with Example 7, after adding silane coupling agent KH550 and polyvinyl alcohol to the graphene oxide dispersion, the water vapor transmission rate and oxygen transmission rate of the finished product decreased significantly, while the interlayer bonding force increased. This proves that the proportion of graphene oxide re-stacking during coating or injection molding is lower, thus improving the barrier effect.

[0076] Furthermore, comparing Examples 10-11 with Example 9, or Examples 10-11 with Examples 12-13, in the preparation of graphene oxide dispersion, adding only silane coupling agent KH550, or adding silane coupling agent KH550 and stabilizer sodium carboxymethyl cellulose, resulted in a lower barrier effect than Example 10-11. This demonstrates that adding silane coupling agent KH550 and polyvinyl alcohol simultaneously during the preparation of graphene oxide dispersion has superior technical effects.

[0077] Fourth, PLA stepwise gradient injection molding can protect the graphene oxide layer. Comparing Examples 6-8 with Examples 1-3, PLA stepwise gradient injection molding can protect the graphene oxide layer, making it more stable during the injection molding process, thereby promoting the improvement of the barrier properties of the finished product, such as reducing parameters like water vapor permeability and oxygen permeability.

[0078] However, comparing Example 7 and Comparative Example 6, when the primary and secondary injection molding conditions of PLA are similar, they cannot effectively protect the graphene oxide layer, and the technical performance of the product shows a downward trend, proving that the primary injection molding conditions have an impact on the properties of the finished product.

[0079] It should be added that the injection molding holding pressure time is extremely short, and the actual temperature field on the PBAT side is gradient-distributed, so it will not melt or damage the GO layer due to the brief high temperature at this time. In actual experiments, there was slight softening on the PBAT interface side, but the GO sheets were pressed firmly onto the PBAT surface under the PLA melt pressure, which is more conducive to interfacial bonding.

[0080] Understandably, in the embodiments of this application, the thin biodegradable material prepared can be directly used in products such as sealed bags and sealed films, or three-dimensional products such as lunch boxes and cups, or can be attached to the inside or outside of three-dimensional products to improve barrier performance.

[0081] In summary, the biodegradable materials, three-dimensional products, and their preparation methods provided by the embodiments of the present invention solve the technical problem of easy agglomeration of GO during melt blending by sequentially compounding PBAT, GO, and PLA, resulting in products with better barrier properties and good application prospects.

[0082] It should be noted that, for those skilled in the art, the technical features in the above embodiments can be freely combined, and the resulting technical solutions also belong to the embodiments disclosed in this application.

[0083] Furthermore, without departing from the principles of this application, several improvements and modifications may be made to this application, and these improvements and modifications also fall within the protection scope of the claims of this application.

Claims

1. A biodegradable material, characterized in that, include: The base includes a PBAT layer and a graphene oxide layer located on the first surface of the PBAT layer; Structural components, including the PLA layer; The PLA layer and the PBAT layer are bonded together by a graphene oxide layer.

2. The biodegradable material according to claim 1, characterized in that, In the biodegradable material, by mass fraction, the PBAT layer comprises 30-70 parts and the graphene oxide layer comprises 0.1-1 parts.

3. The biodegradable material according to claim 2, characterized in that, The thickness of the PBAT layer is 10-100 μm, and / or the thickness of the graphene oxide barrier layer is 50-200 nm.

4. A method for preparing a biodegradable material as described in any one of claims 1-3, characterized in that, Including the following steps: To prepare a graphene oxide dispersion, graphene oxide powder was dispersed in a solvent and ultrasonically treated to obtain a uniform graphene oxide dispersion with a concentration of 1-1.8 mg / mL. Graphene oxide coating: The graphene oxide dispersion is applied at a concentration of 5-10 g / m³. 2 The PBAT substrate film is uniformly coated on the surface of the PBAT film, and the solvent is removed by drying. A graphene oxide barrier layer is formed on the surface of the PBAT film to obtain a PBAT / GO composite film, or substrate. Pre-forming involves placing the PBAT / GO composite film inside the cavity of an injection mold, ensuring the composite film adheres tightly to the inner wall of the mold to form a pre-formed body that matches the shape of the mold; the graphene oxide barrier layer of the composite film faces the inner side of the mold cavity. PLA is fused together by injecting PLA melt into a mold with PBAT / GO composite film bonded together, so that PLA melt comes into contact with the surface of the graphene oxide barrier layer of the preform. Under the action of injection pressure and temperature, PLA melt and PBAT / GO composite film are tightly bonded together. After cooling, the mold is removed to obtain a laminated three-dimensional product including a base and structural parts.

5. The method for preparing the biodegradable material according to claim 4, characterized in that, Including the following steps: In the step of preparing graphene oxide dispersion, the ultrasonic frequency is 68-120 kHz and the ultrasonic time is 1-3 h.

6. The method for preparing the biodegradable material according to claim 4, characterized in that, In the step of preparing graphene oxide dispersion, after uniformly dispersing graphene oxide powder in deionized water, 0.5-0.8 wt% of silane coupling agent KH550 and 0.1-0.2 wt% of polyvinyl alcohol are added, and the mixture is ultrasonicated at a frequency of 68-120 kHz for 1-3 hours.

7. The method for preparing the biodegradable material according to claim 4, characterized in that, In the graphene oxide coating step, the thickness of the graphene oxide barrier layer formed on the surface of the PBAT film is 50-200 nm.

8. The method for preparing the biodegradable material according to claim 7, characterized in that, After the graphene oxide coating step, the obtained PBAT / GO composite film is subjected to unidirectional or bidirectional stretching treatment at 60-90℃ with a stretching rate of 1.5-2 times, so that the graphene oxide sheets are oriented and aligned in the film plane.

9. A three-dimensional article prepared from the biodegradable material according to any one of claims 1-3.

10. A three-dimensional article prepared from a biodegradable material obtained by any one of claims 4-8.